Cancer Neuroscience - Amit, Moran; Scheff, Nicole N. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This volume is the first on the market to address and discuss the emerging field of cancer neuroscience. Edited by pioneers in the field with contributions from top researchers, the volume serves as a comprehensive overview of the role of nerves in tumorigenesis and cancer progression. Chapters will address how the innervation of tumors can serve as both prognostic and predictive biomarkers as well as actionable therapeutic targets. Authors will describe current research efforts, and future directions for study and translation to the clinic. It is becoming increasingly apparent that certain treatments will need to consider interactions between the nervous system and cancer, and the novel concepts presented in the book address related accumulating evidence regarding therapeutic strategies. This unique volume will be useful for cancer researchers, neuroscientists, cancer biologists, oncologists, and others looking to gain a greater understanding of this emerging field.
Chapter 1. Introduction -- Chapter 2. Neuronal influence on cancer initiation and growth -- Chapter 2.1 Paracrine signaling in CNS primary tumors and brain metastases -- Chapter 2.2 Paracrine signaling in PNS primary tumors -- Chapter 3. Neuronal influence on cancer invasion and metastasis including perineurial invasion -- Chapter 4. Neurotrophic activity of tumors -- Chapter 5. Cancer interactions with Schwann cells -- Chapter 6. Cancer-glial interactions -- Chapter 7. Neuron-cancer synaptic and other electrical signaling -- Chapter 8. Neuro-immune interactions system and immuno-oncology -- Chapter 9. Nervous system interactions with non-immune elements in the cancer microenvironment -- Chapter 10. Cancer-induced remodeling of the nervous system -- Chapter 11. Cancer and pain -- Chapter 12. Systemic interactions of cancer and the impact on the nervous system -- Chapter 13. Tools and model systems to study nerve-cancer interactions -- Chapter 14. Conclusions and Future Directions.
Keywords: Cancer; Cancer -- Treatment; Neurosciences; Immunotherapy; Cancer Biology; Cancer Therapy; Neuroscience; Cancer Microenvironment; Immunotherapy